MUTU SIRUP BUAH PEDADA (Sonneratia Caseolaris) SELAMA PENYIMPANAN DENGAN PENAMBAHAN NATRIUM BENZOAT - Denty Andriani; Raswen Efendi; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is to get the best quality of fruit pedada’s syrup during storage with increasing the sodium benzoat. This research use the Complete Random Design (CDR) with 5 treatments of increaseing the sodium benzoat (0%, 0.05%. 0.10%. 0.15%. 0.20%) and each of them is repeated by three times. The parameter which is observed were the level of sedimentation, the content of sucrose, mold growth, pH, viskosity and organoleptic. The value of observation which is got analyzed with statistic. If F aritmatic is greater or equal with F table so done the next test by using Duncan test on 5% level. The results of this research shows that the increasingof sodium benzoat on fruit pedada’s syrup gave the significant effect to the number of pH, the viskosity , content of sucrose, sedimentation and mold growth organoleptic more decreased. From the results of research which have done, got the average values of sucrose’s content is 73.50 to 79.92, the degree of acidity (pH) is 4.60 to 4.71, of sedimentation is 10.91 to 14.85, viskosity from 177,54 to 202,40 and on S3. S4, and S5 three’s no growth mold to the syrup which is peoduced during storage. Keyword : Syrup, Fruit Pedada, Sodium Benzoat